Avaliação do potencial de transmissibilidade de leishmaniose visceral em primatas-não-humanos de cativeiro da região metropolitana de Belo Horizonte – MG - Ayisa Rodrigues de Oliveira (2019)
Leishmaniasis is a zoonotic disease of worldwide relevance. In Brazil, visceral leishmaniasis is endemic and caused by Leishmania infantum (synonym Leishmania chagasi) with Lutzomyia longipalpis being the most important invertebrate vector. Non-human primates can be infected with L. infantum, however, little is known about the role of these species as reservoirs. Fifty two non-human primates kept in captivity in Belo Horizonte, an endemic area for visceral leishmaniasis, were subjected to xenodignosis. Anti-Leishmania serologic tests were performed on all animals included in the study. Sand flies fed on all animals were tested by qPCR to identify and quantify L. infantum promastigotes. Eight of the 52 non-human primates were positive by xenodiagnosis, including three Pan troglodytes, three Leontopithecus rosalia, one Sapajus apella, and one Miopithecus talapoin, and seven of them were also positive at serology. Estimated numbers of 5.67 to 1,181.93 promastigotes/μg of DNA were observed. Positive animals had higher levels of IgG anti-Lu. longipalpis saliva when compared to negative animals, prior to xenodiagnosis. Captive non-human primates are capable of infecting Lu. longipalpis with L. infantum, been a potential reservoir and possible playing a role in the maintenance of this agent in the environment in endemic areas. Our findings also demonstrate the relevance of non-human primates as sentinels to zoonotic diseases. This study has implications for public health strategies and under a conservation medicine perspective.